Antimicrobial activity of n-hexane and ethyl acetate extracts from Candida tropicalis and Phyllosticta capitalensis fungal endophytes - Fulgence N. Mpenda; Mwanaisha Mkangara (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background ad objective: Among the notable achievements of the twentieth century was the discovery and identification of new drugs from plants against microbial infections. However, the discovery of novel drugs since then is inadequate due to emergence of resistant microbes. In an effort to discover novel drugs, the study aimed to investigate the antimicrobial activity of crude extracts from endophytic fungi isolated from Cnidoscolas aconitifolius and Ocimum suave.